Theoretical analysis of a regenerative supercritical carbon dioxide Brayton cycle/organic Rankine cycle dual loop for waste heat recovery of a diesel/natural gas dual-fuel engine. (1st October 2019) - Liang, Youcai; Bian, Xingyan; Qian, Weiwei; Pan, Mingzhang; Ban, Zhibo; Yu, Zhibin
Highlights: Demonstrated a novel waste heat recovery system with higher efficiency. It integrates a regenerative supercritical carbon dioxide Brayton cycle with an Organic Rankine cycle. It avoids the decomposition problem for high temperature waste heat recovery. The engine power output with waste heat recovery can be improved by 6.78%. Abstract: Supercritical carbon dioxide Brayton cycle is considered one of the most promising systems for waste heat recovery of engines because of its compactness and high energy efficiency. To further improve the fuel utilization ratio and solve the difficulties of waste heat recovery of high temperature exhaust gas, a regenerative supercritical carbon dioxide Brayton cycle/organic Rankine cycle dual loop is proposed for cascade utilization of exhaust heat from a dual-fuel engine. The regenerative supercritical carbon dioxide Brayton cycle of the proposed system is powered by the waste heat contained in the exhaust gas. The working fluid in the organic Rankine cycle is pre-heated by CO2 exiting the regenerator and then further heated by the residual heat of the exhaust gas. The flow rates of the working fluids in both sub cycles are adjusted to match the waste heat recovery system to respond to the changing conditions of the dual-fuel engine. The results revealed that the maximum net power output of this system is up to 40.88 kW, thus improving the dual-fuel engine power output by 6.78%. Therefore, such a regenerative supercritical carbon dioxide Brayton cycle/organic Rankine cycle dual loop system design enables the thorough recovery of high temperature exhaust heat, leading to higher energy efficiency and lower fuel consumption of the engine.